HIV Rebound Is Predominantly Fueled by Genetically Identical Viral Expansions from Diverse Reservoirs - De Scheerder, Marie-Angélique; Vrancken, Bram; Dellicour, Simon; Schlub, Timothy; Lee, Eunok; Shao, Wei; Rutsaert, Sofie; Verhofstede, Chris; Kerre, Tessa; Malfait, Thomas; Hemelsoet, Dimitri; Coppens, Marc; et al. (Cell host & microbe, 2019)
Viral rebound upon stopping combined antiretroviral therapy poses a major barrier toward an HIV cure. Cellular and anatomical sources responsible for reinitiating viral replication remain a subject of ardent debate, despite extensive research efforts. To unravel the source of rebounding viruses, we conducted a large-scale HIV-STAR (HIV-1 sequencing before analytical treatment interruption to identify the anatomically relevant HIV reservoir) clinical trial. We collected samples from 11 participants and compared the genetic composition of (pro)viruses collected under treatment from different cellular and anatomical compartments with that of plasma viruses sampled during analytical treatment interruption. We found a remarkably heterogeneous source of viral rebound. In addition, irrespective of the compartment or cell subset, genetically identical viral expansions played a significant role in viral rebound. Our study suggests that although there does not seem to be a primary source for rebound HIV, cellular proliferation is an important driver of HIV persistence and should therefore be considered in future curative strategies. [Display omitted] •HIV-1 sequences sampled from different reservoirs were compared to rebound viruses in 11 individuals•Rebound viruses can originate from various cellular and anatomical compartments•Cellular proliferation is an important driver of HIV persistence•Cure strategies should take into account the lack of a prominent HIV rebound origin De Scheerder et al. conduct an in-depth investigation into the origins of HIV rebound. They show that viral rebound originates from multiple compartments and cell proliferation is a driver of viral persistence. Future HIV cure strategies will need to overcome the challenges associated with heterogeneous viral rebound.